Congenital hypothyroidism in pediatric practice - A. V. Vitebskaya (Медицинский совет, 2016)
We present observation of two patients with congenital hypothyroidism. Importance of neonatal screening for congenital hypothyroidism is demonstrated.The main principles of diagnostics, therapy and dispensary supervision, role of pediatricians in observation of patients with congenital hypothyroidism are described.